Dissents in Regulating Cultural Trade and Its Mechanisms of Dispute Settlements in Multilateral Forum: Analyzing the Roles of UNESCO and WTO - Annisa Pratamasari (Global Strategis, 2019)
Even though the volume of trade in goods and service increases in some advanced economy countries, trade in cultural goods and services remain in neglected terrain within multilateral frameworks. WTO has indeed highlighted the importance of cultural goods’ protection; however, its meaning and scopes, terms of protection, and dispute settlement on cultural goods and services have remained vague. On the other hand, UNESCO shed some lights on the trade of cultural goods and services, but some of the articles in its convention arises some contradiction with WTO clauses. The cases presented in this paper are all related to the culture trade, namely Canada for a periodical case (DS31), Turkey’s taxation of foreign film (DS43), Canada’s case on film distribution service (DS117), and China’s case on publications and audiovisual products (DS363). This paper aims to analyze how those cases were handled in the dispute settlement of WTO and supposed to be handled by both UNESCO and WTO. I would like to draw some lessons from the inadequate dispute settlement in WTO on culture trade, then proceed to formulate some suggestions of how cultural trade-related disputes are supposed to be formulated.